The Antibiotic Cement Bead Rouleaux: A Technical Trick to Maximize the Surface Area to Volume Ratio of Cement Beads to Improve the Elution of Antibiotics. Issue 9 (September 2022) - Perry, Nicholas P.J.; Tucker, Nicholas J.; Hadeed, Michael M.; Heare, Austin; Stacey, Stephen C.; Hammerberg, E. Mark; Mauffrey, Cyril; Parry, Joshua A.
Summary: The use of antibiotic-impregnated cement as a local antibiotic delivery system is well-established as an adjunctive treatment for chronic osteomyelitis. Because the elution of antibiotics is a surface area phenomenon, the geometry of the cement is an important consideration. The antibiotic cement bead rouleaux technique is a simple and efficient method of bead fabrication that requires only 10 minutes of preparation time and readily available operating room supplies. The discoid structure of the beads provides 3 times the surface-area-to-volume ratio of a spherical bead, which facilitates antibiotic elution. Given the speed and ease of fabrication, along with optimized geometry, the antibiotic cement bead rouleaux is a useful addition to the surgeon's repertoire.